Durability Assessment of Green Concrete Incorporating Volcanic Tuff Pozzolan, Basalt, and Recycled Aggregate - Wassouf, Moustafa A.; Omran, Jamal Y.; Kheirbek, Ali I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Extending the lifespan of building structures is a critical strategy for mitigating environmental impacts, particularly greenhouse gas emissions from cement production, like emissions from cement. Green concrete, made from pozzolana, basalt, and recycled materials, was tested for durability. Samples were immersed in 2% sulfuric acid for a week, then checked for resistance loss. This study investigates the performance of various concrete mixtures through experiments and simulations where Portland Cement was replaced by natural pozzolana ground into the bonding paste in proportions ranging from 10% to 50% with the use of four types of gravel structures I (natural gravel), II (recycled gravel), III (pozzolanic gravel with basalt sand), and IV (pozzolanic gravel and sand), where 128 cubes were poured with dimensions (10 × 10 × 10) cm to perform simple pressure tests on samples before and after immersion in a solution of sulfuric acid. The results showed that higher cement replacement percentages in mixtures with recycled aggregates resulted in greater durability reduction, with resistance losses exceeding 34% at 50% replacement, primarily due to the rounded aggregate morphology and lower acid resistance. In contrast, mixtures incorporating pozzolanic gravel and basalt sand showed superior performance, achieving only 18.7% resistance loss at 50% replacement (compared to 30.1% at lower replacement rates), highlighting basalt’s effective pore-filling capability. The optimal performance was observed in pozzolanic gravel-sand blends, which exhibited just 13.7% resistance loss, demonstrating enhanced synergistic pozzolanic activity. These findings validate that optimized pozzolana-basalt combinations significantly improve chemical resistance, offering promising solutions for sustainable concrete development.